A Vision of the European Union: A Study of Media Coverage of Polish Election Campaigns for the 2019 European Parliament Elections - Stasiak-Jazukiewicz, Ewa; Jas-Koziarkiewicz, Marta; Mienkowska - Norkiene, Renata (Politologija, 2020)
The 2019 European Parliament (EP) elections coincided with the discussions about the need to change the European integration model. These discussions were forced by the refugee crisis and Brexit. In this article, the authors investigate the media representation of programs proposed by Polish political parties in the campaign for EP 2019 elections. The purpose is to determine how the media reported on these programs (media agenda). The research question required the supplementation of the study with an analysis of the political parties’ programs. The research model is based on an agenda-setting theory. The empirical section presents the results of the quantitative and qualitative analysis of both media and political agendas, confirming the discrepancy between them.